PERBEDAAN KADAR GULA DARAH TERHADAP SENAM KAKI PENDERITA DIABETES MELLITUS DI PUSKESMAS GONDOKUSUMAN I YOGYAKARTA - Nur Yeti Syarifah; Muryani Muryani (STIKES Wira Husada Yogyakarta, 2018)
ABSTRACT Background: Diabetics Mellitus in the world from year to year show an increase. Based on the data from international diabetes federation 2015, there Diabetics Mellitus as many as 387 million lives in 2014 increased to 415 million lives in 2015 and is expected to grow up to 642 million people in the 2040. Indonesia are placed 7th in the world of 10 million people, Incidence Diabetics Mellitus based on the results of health research for basic D.I Yogyakarta (2013) showed that Diabetics Mellitus highest occurred in the town of Yogyakarta as many as 3.4%. Data from the health department city Yogyakarta for Diabetics Mellitus most found in the Health Center Gondokusuman I namely by the number of 387 cases of Diabetics Mellitus. Exercise physical or sport is advisable one of them is gymnastic feet Diabetics Mellitus. Gymnastic feet aimed at improving circulation blood and nutrients to tissues as in smoothly. The purpose of: to know the inﬂ uence of gymnastic the foot against the blood sugar levels in people with Diabetics Mellitus.A method of: the research is quantitative research, uses the method pre eksperiment design it is the this research that is used is identiﬁ cation one group pretest and posttest with both 17 respondents in the present study. The results of: the results of the analysis bivariate by the use of what is the formula Wilcoxon shows differences in blood sugar levels before and after gymnastic feet , and also showed the presence of the inﬂ uence of gymnastic the foot against the blood sugar concentration patients Diabetics Mellitus with the value of p value 0.001. A conclusion: there is a difference in blood sugar levels before and after gymnastic feet, and also showed the presence of the inﬂ uence of gymnastic the foot against the blood sugar concentration patients Diabetes Mellitus.